Successful pregnancy outcome in a case of Takayasu’s arteritis with recurrent pregnancy loss with low dose heparin - Khandelwal, Richi; Gandhi, Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Takayasu's arteritis (TA) is a well-known yet rare form of large vessel vasculitis. TA commonly effect women in childbearing age of Asian origin. The etiology remains speculative but current literature supports autoimmune basis for TA. Suppression of inflammation and preservation of vascular competence form the basis of the treatment. The basic disease appears to be unaffected by pregnancy, inflammatory activity and haemodynamic status improves with pregnancy, but the high arterial pressure and the pre-eclampsia constitute main maternal complications. The fetal complication is intrauterine growth. Therefore, obstetricians are faced with the dilemma of optimal management in pregnancy. The optimum management of these women involves conception during the remission period, antenatal care provided by multidisciplinary team, early detection, treatment of hypertension and curtailing the second stage of labour for better maternal and fetal outcome. In our case, the patient was managed with low dose heparin which was started as soon as the patient visited us (14 weeks) and continued till one day before surgery. No steroids were given at any time during the course of pregnancy and post - one year follow - up the patient is doing fine.